(MCTS) Microsoft BizTalk Server 2010 (70-595) certification guide : including Microsoft partner network technical competency assessment for application integration (BizTalk Server 2013) and Windows Azure Biztalk services coverage /: including Microsoft partner network technical competency assessment for application integration (BizTalk Server 2013) and Windows Azure Biztalk services coverage. (2014) - Hedberg, Johan; Cour, Morten la; Weare, Kent
No abstract available